Prison research: a bioethics or an ethics issue? - Fanega, Manuel (Acta Bioethica, 2021)
The hypothesis of reducing aggressiveness through transcranial direct current stimulation was recently tested on a cohort of inmates in Spain. The experiment, including 1.5 mA electric shocks, was an external research initiative that received the initial acquiescence of the carceral system. An alarm was raised at the time the research was published, encouraging the directorate of prisons to stop the ongoing replication of the experiment. Nevertheless, no (bio)ethics committee, in the universities or among bioethics experts, has questioned the research. In this think piece, we aim to again discuss some ethical approaches to these clinical interventions on crime. After its positivistic period, the field of criminology has been questioning the simple psychobiological approach to crime because of the reductionistic view of this phenomenon and its harmful consequences. Thus, we address academic experimentation under prison governance and the “re” roles of prisons. We argue that the minor disadvantages of such research, if performed with consent, could be positive if the research can minimize the harmfulness of prison itself; thus, penitentiary treatment and science should go together. Prison administrations, in addition to their duty to protect the individuals under their control from ethically biased research, must promote reintegration. We conclude that human rights are over criminal policy and science and that ethics are over narrower bioethics.